The Clean Text - Rabello, Adylla Rocha (Manuscrítica: Revista de Crítica Genética, 1992)
In 1976, José Américo de Almeida publishes his last book of memories called "Antes que eu me esqueça" in which he tells stories about his childhood. In an introductory note, he said that he refused the first text he had written because he did not like it. After the original manuscript had been found in his archives, we discovered that it worked as a guideline for the published work. In this study, we compare one of the paragraphs of the manuscript and the corresponding chapter in the published text, to see the modifications that were made by the author in the process of re-creation.